The Pursuit of Painting - Irish Museum of Modern Art, Dublin; Albert, Hermann; Baer, Jo; Balthus; Bonnard, Pierre; Bradley, Fiona; De Chirico, Giorgio; Derain, André; Freud, Lucian; Goller, Bruno; Gris, Juan; Heaney, Seamus; et al. (London : Lund Humphries Publishers, 1997)
Albert, Hermann ; Baer, Jo ; Balthus ; Bonnard, Pierre ; De Chirico, Giorgio ; Derain, André ; Egan, Felim ; Eun-Mo, Chung ; Freud, Lucian ; Goller, Bruno ; Gorman, Richard ; Gris, Juan ; Hélion, Jean ; John, Gwen ; Leger, Fernand ; Lennon, Ciaran ; Lüpertz, Markus ; Malevich, Kasimir ; McComb, Leonard ; Morandi, Giorgio ; Picabia, Francis ; Rego, Paula ; Schermuly, Peter ; Scully, Sean ; Williams, Michael ; Yeats, Jack B.
biografie
The pursuit of painting, Irish Museum of Modern Art, Dublin, 26 June - 2 November 1997
Duits
Engels
Frans
Italiaans